2008
DOI: 10.15628/holos.2008.187
|View full text |Cite
|
Sign up to set email alerts
|

A Prática Pedagógica Do Ensino De Educação Ambiental Nas Escolas Públicas De João Câmara – Rn

Abstract: O presente projeto de pesquisa foi desenvolvido em três escolas públicas (Cenecista João XXIII, Francisco de Assis Bittencourt e Antônio Gomes) da cidade de João Câmara-RN, com o objetivo geral de conhecer a realidade dessas escolas, no sentido de saber se existe uma prática permanente das questões ambientais nos currículos escolares e se estes são passados aos alunos de forma multidisciplinar, como determina os Parâmetros Curriculares Nacionais – PCNs, que dá evidência necessária a preservação do meio ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
0
0
8
Order By: Relevance
“…At the same time, 100% of professors are interested in working on EE in an interdisciplinary way. This result is similar to Saraiva et al, (2008) who showed that around 70% of teachers at the João Câmara school in Rio Grande do Norte practice EE, despite being aware that the practice would be easier if the school had a pedagogical political project. While Gomes (2011) shows in his research that municipal managers should strengthen the training of teachers in this subject, mainly guided by a critical view, due to the complexity of the subject.…”
Section: Resultssupporting
confidence: 87%
“…At the same time, 100% of professors are interested in working on EE in an interdisciplinary way. This result is similar to Saraiva et al, (2008) who showed that around 70% of teachers at the João Câmara school in Rio Grande do Norte practice EE, despite being aware that the practice would be easier if the school had a pedagogical political project. While Gomes (2011) shows in his research that municipal managers should strengthen the training of teachers in this subject, mainly guided by a critical view, due to the complexity of the subject.…”
Section: Resultssupporting
confidence: 87%
“…O processo que envolve e De acordo com Silva e Leite ( 2008) para a inserção da Educação Ambiental nas escolas, as seguintes estratégias são necessárias: identificar a percepção ambiental dos indivíduos envolvidos; obter um diagnóstico ambiental do centro de ensino, bem como do seu entorno; investir na formação dos docentes e; utilizar metodologias didáticas que permitam a construção do conhecimento de forma dinâmica, criativa, crítica, lúdica, participativa e investigativa. Os professores devem se empenhar na aplicação da Educação Ambiental de forma prática, não somente de forma teórica, destituindo-a do posto de ser apenas um eixo transversal e tornando-a como um dos principais temas trabalhados nos processos educativos (SARAIVA; COSTA, 2008).…”
Section: Resultsunclassified
“…Compte tenu de l'importance de ce thème, plusieurs études ont été trouvées dans la littérature qui l'analysent à travers différentes approches. En voici quelques-unes : pratiques interdisciplinaires (NOGUEIRA et MEGID NETO, 2020;BURSZTYN, 2004;CONRADO et SILVA, 2017); formation des enseignants (BARROS, QUEIROS et SOUZA, 2019;VALENTIM et CARVALHO, 2020); manuels (MARPICA et LOGAREZZI, 2010;SULEIMAN et ZANCUL, 2012;OLIVEIRA et VIVIANI, 2009;GROSSI, 2004;MELLO et LONGHINI, 2013); pratiques pédagogiques (SILVA et TERÁN, 2018;SARAIVA, NASCIMENTO et COSTA, 2008;POLLI;SIGNORINI, 2012).…”
Section: Introductionunclassified